(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This article aims to look at the relationship between religious freedom and social security in the European Union, by looking at the first judgment of the Court of Justice of the European Union concerning Jehovah’s Witnesses’ refusal to undergo blood transfusions. It challenges the prevailing economy-based approach insofar as it does not strike an appropriate balance with the respect for fundamental freedoms. It also questions the assumption that there is an opposition between the allegedly subjective religious principles and practices and the objective medical conditions.